inverse taylor series inverse $\sum \limits_{k\ge 1} \frac{(-1)^{k-1}}{z+k}$

Given $\sum \limits_{k\ge 1} \frac{(-1)^{k-1}}{z+k}$, how do we find the function f that corresponds to this series? How do we find the taylor series of f in the point $z=0$ ?

Thank you very much for every input. xD

-

Let's split the sum into even and odd parts: $\sum \limits_{k \geqslant 1} \frac{(-1)^{k-1}}{z+k} = \sum \limits_{k \geqslant 0} \left( \frac{1}{z+2 k +1} - \frac{1}{z+2 k +2} \right) = \sum_{k \geqslant 0} \left( \left( \frac{1}{z+2 k +1} - \frac{1}{2k+2} \right) - \left( \frac{1}{z+2 k +2} - \frac{1}{2k+2} \right) \right)$.
Notice that $\sum \limits_{k \geqslant 0} \left( \frac{1}{z+2 k +1} - \frac{1}{2k+2} \right) = \frac{1}{2} \sum \limits_{k \geqslant 0} \left( \frac{1}{k + (1+z)/2} - \frac{1}{k+1} \right) = -\frac{1}{2} \psi\left(\frac{1+z}{2} \right)$, where $\psi(z)$ is the digamma function.
Likewise $\sum \limits_{k \geqslant 0} \left( \frac{1}{z+2 k +2} - \frac{1}{2k+2} \right) = -\frac{1}{2} \psi\left(\frac{z}{2} + 1\right)$.
Thus $$\sum_{k \geqslant 1} \frac{(-1)^{k-1}}{z+k} = \frac{1}{2} \left( \psi\left(\frac{z}{2} + 1\right) - \psi\left(\frac{1+z}{2} \right) \right)$$
The Taylor series around $z=0$ actually follows from the defining series: $$[z]^m \sum_{k \geqslant 1} \frac{(-1)^{k-1}}{z+k} = \sum_{k \geqslant 1} \frac{(-1)^{k+m+1}}{k^m} = (-1)^{m+1} \left(1- 2^{-m} \right) \zeta(m+1)$$ thus $$\frac{1}{2} \left( \psi\left(\frac{z}{2} + 1\right) - \psi\left(\frac{1+z}{2} \right) \right) = \sum_{m=0}^\infty (-1)^{m+1} \left(1- 2^{-m} \right) \zeta(m+1) z^m$$